Microbial biofilms and gastrointestinal diseases. Issue 1 (29th January 2013) - von, Erik C.; O'May, Graeme A.; Macfarlane, Sandra; Macfarlane, George T.; Shirtliff, Mark E.
Abstract The majority of bacteria live not planktonically, but as residents of sessile biofilm communities. Such populations have been defined as 'matrix‐enclosed microbial accretions, which adhere to both biological and nonbiological surfaces'. Bacterial formation of biofilm is implicated in many chronic disease states. Growth in this mode promotes survival by increasing community recalcitrance to clearance by host immune effectors and therapeutic antimicrobials. The human gastrointestinal (GI) tract encompasses a plethora of nutritional and physicochemical environments, many of which are ideal for biofilm formation and survival. However, little is known of the nature, function, and clinical relevance of these communities. This review summarizes current knowledge of the composition and association with health and disease of biofilm communities in the GI tract.